Supporting In-Home Caregivers in Symptom Assessment of Frail Older Adults with Serious Illness: A Pilot Study - Nouri, Sarah (J Palliat Med, 2020)
Background: Many older adults with serious illness who depend on others for care have symptoms that are difficult to manage. Supporting caregivers in symptom assessment (SA) may reduce suffering. Objective: Pilot an SA-Toolkit for caregivers to assess older adults' symptoms at home. Design: Pilot study. Setting/Subjects: English-speaking patients ≥65 years of age and their caregivers from a home-based geriatrics program in San Francisco. Measurements: With multiple stakeholder input, we created a SA-Toolkit consisting of illustrations depicting symptoms, validated Faces Scale, and easy-to-use tracking system with phone numbers of family/friends/clinicians. At baseline and one week, we assessed change in patients' symptoms and caregivers' self-efficacy with SA (5-point scale) using Wilcoxon signed-rank tests. We assessed acceptability at one week. Results: Eleven patient/caregiver dyads participated in the study. Patients were 84.7 years old (SD 5.7), 81.8% women, 27.3% non-white. From baseline to one week, mean number of symptoms decreased (3.7 [1.5] to 2.6 [1.8], p = 0.03). Specifically, patients with pain decreased from 63.6% to 36.4%, anxiety 54.6% to 18.2%, depression 45.5% to 27.3%, and loneliness 36.4% to 18.2%. Caregiver self-efficacy increased (4.6 [0.3] to 4.8 [0.3], p = 0.09). Patients found the symptom illustrations easy to use (8.7 on 10-point scale), but the Faces Scale less so (7.3/10) because it provided “too many choices.” Caregivers liked the SA-Toolkit because it was easy to use; nearly all (10/11, 90%) would recommend it to others. Conclusions: The SA-Toolkit resulted in decreased symptom burden among patients and higher caregiver self-efficacy in SA. The SA-Toolkit is acceptable and may help reduce suffering in frail, older patients.